NESTED TAYLOR DECOMPOSITION IN MULTIVARIATE FUNCTION DECOMPOSITION - GÜRVİT, ERCAN (AMER INST PHYSICS, 2014)
Fluctuationlessness approximation applied to the remainder term of a Taylor decomposition expressed in integral form is already used in many articles. Some forms of multi-point Taylor expansion also are considered in some articles. This work is somehow a combination these where the Taylor decomposition of a function is taken where the remainder is expressed in integral form. Then the integrand is decomposed to Taylor again, not necessarily around the same point as the first decomposition and a second remainder is obtained. After taking into consideration the necessary change of variables and converting the integration limits to the universal [0; 1] interval a multiple integration system formed by a multivariate function is formed. Then it is intended to apply the Fluctuationlessness approximation to each of these integrals one by one and get better results as compared with the single node Taylor decomposition on which the Fluctuationlessness is applied.
Keywords: Taylor decomposition; Multi-point Taylor expansion; Nested Taylor decomposition; Multivariate functions; Univariate function approximation; FLUCTUATIONLESSNESS THEOREM; INTEGRATION; REMAINDER